Dolphin-Watching Boats Affect Whistle Frequency Modulation in Bottlenose Dolphins - Perez-Ortega, Betzi; Daw, Rebecca; Paradee, Brennan; Gimbrere, Emma; May-Collado, Laura J. (Frontiers in Marine Science, 2021)
Bottlenose dolphins’ whistles are key in social communication, conveying information about conspecifics and the environment. Therefore, their study can help to infer habitat use and identify areas of concern due to human activities. Here we studied the whistles of bottlenose dolphins (Tursiops truncatus) in two sites of the archipelago of Bocas del Toro, Panama, that contrast in boat traffic. Almirante Bay is a site dominated by taxi-boats and Dolphin Bay is a major location for boat-based dolphin watching. Recordings were made using bottom-mounted hydrophones and from the research boat using an over-the-side hydrophone and a broadband recording system. A total recording effort time of 1,726 h was analyzed. Our results show significant differences in boat detection between sites, and a higher number of whistles detected per minute in the site with tour-boat traffic. Furthermore, whistle modulation accounted for most of the differences between sites, boat presence, and whistle types. Dolphin whistle modulation is thought to be a potential indicator of emotional states including danger, alertness, and stress. In this study, dolphin signature whistle modulation increased significantly with boat presence in both sites but changes in modulation were greater in Dolphin Bay where tour-boats directly and sometimes aggressively interact with the animals. These results support a potential association between whistle modulation and stress (or alertness). These findings indicate that if tour-boat captains behave more like taxi-boat captains by e.g., reducing the distance of approach and contact time during dolphin interactions, dolphin communication, and emotional state would be less disrupted. These measures are implemented in the national guidelines for whale-watching and are known to tour-boat operators. The key to protecting these dolphins is in finding ways to effectively enforce these operator guidelines.